2016
DOI: 10.1097/iop.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Phenomenon With Involutional Ptosis

Abstract: Frontalis contraction is observed when acute ptosis is simulated in anophthalmic patients, confirming that a contracted visual field cannot be the only stimulus for compensatory brow elevation. A sensory or proprioceptive mechanism is suggested but not confirmed by the trend of reduction in brow elevation with topical anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Ipsilateral frontalis muscle activation in anophthalmic patients with ptosis is an interesting phenomenon that demonstrates the presence of non-visual stimuli in frontalis recruitment, showing that a sensory trigger - and not a visual stimulus - might be responsible for frontalis recruitment in these patients. 81 , 82 Histologic studies have confirmed the presence of Golgi tendon organs, muscle spindles, and myotendinous cylinders within the levator muscle, 83 and neural structures have been demonstrated in Müller’s muscle fibers. 84 These nerve terminals may be implicated in proprioception, and the pathway for frontalis contraction might originate in proprioceptive fibers in the Müller’s muscle through the trigeminal ganglion.…”
Section: Ptosis In Anophthalmic Patientsmentioning
confidence: 88%
See 1 more Smart Citation
“…Ipsilateral frontalis muscle activation in anophthalmic patients with ptosis is an interesting phenomenon that demonstrates the presence of non-visual stimuli in frontalis recruitment, showing that a sensory trigger - and not a visual stimulus - might be responsible for frontalis recruitment in these patients. 81 , 82 Histologic studies have confirmed the presence of Golgi tendon organs, muscle spindles, and myotendinous cylinders within the levator muscle, 83 and neural structures have been demonstrated in Müller’s muscle fibers. 84 These nerve terminals may be implicated in proprioception, and the pathway for frontalis contraction might originate in proprioceptive fibers in the Müller’s muscle through the trigeminal ganglion.…”
Section: Ptosis In Anophthalmic Patientsmentioning
confidence: 88%
“… 84 These nerve terminals may be implicated in proprioception, and the pathway for frontalis contraction might originate in proprioceptive fibers in the Müller’s muscle through the trigeminal ganglion. 82 The eyelid, in close contact with the prosthesis, may provide an alternative pathway to stimulate ipsilateral frontalis recruitment. 83–85 …”
Section: Ptosis In Anophthalmic Patientsmentioning
confidence: 99%
“…Segal et al attributed this response to possible proprioceptive fibers in Mueller muscle, as the authors were able to stimulate brow elevation by inducing ptosis with an external upper eyelid weight in anophthalmic patients. 7 In a similar project, Beaulieu et al caused ipsilateral brow elevation by placement of an upper eyelid weight in sighted patients. 9…”
Section: Discussionmentioning
confidence: 99%
“…Segal et al attributed this response to possible proprioceptive fibers in Mueller muscle, as the authors were able to stimulate brow elevation by inducing ptosis with an external upper eyelid weight in anophthalmic patients. 7 In a similar project, Beaulieu et al caused ipsilateral brow elevation by placement of an upper eyelid weight in sighted patients. 9 In the current study population, preoperative ipsilateral eyebrow elevation was common in patients undergoing enucleation, with many having bilateral symmetrically elevated brows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation